PENGARUH MODEL KOOPERATIF TIPE NHT BERBANTUAN FLIPBOOK TERHADAP HASIL BELAJAR MATERI SISTEM PEREDARAN DARAH - Natalia, Agus; Putri Panjaitan, Ruqiah Ganda; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe study aimed to determine the effect of cooperative learning model of numbered heads together (NHT) assisted flipbook on student learning outcomes in the material of the human circulatory system in class VIII of SMPN 14 Pontianak. The study used Quasi ekperimental Design with nonequivalent control group design. The sampel of the study consisted of two classes : class VIII H as an experimental group and class VIII I as a control group. The sampling technique was purposive sampling. The instrumen used were 20 multiple choice questions. The average score of the experimental group’s learning outcome was 14,57 while that of control group’s learning outcome was 13,74. The test result of U Mann Whitney showed Zcount < Ztable (-2,13 < - 1,96) which means that there is a discrepancy in learning outcomes of students who were taught with cooperative learning of numbered heads together (NHT) assisted flipbook and those who are taught with conventional model. Through calculation of effect size, cooperative learning model of numbered heads together (NHT) assisted flipbook gave an impact 14,80% on learning outcomes of students of class VIII SMPN 14 Pontianak.  Keywords: cooperative model of numbered heads together, the human circulatory system,  learning outcome.